2021
DOI: 10.5713/ajas.20.0384
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone regulates key factors of the Kelch-like erythroid cell-derived protein with CNC homology-associated protein 1–nuclear factor erythroid 2-related factor 2 signaling pathway in duodenum of post-weaning gilts

Abstract: Objective: This study explored the mechanism of the Kelch-like erythroid cell-derived protein with CNC homology-associated protein 1 (Keap1)-nuclear factor erythroid 2-related factor (Nrf2) signaling pathway under conditions of ZEA-induced oxidative stress in the duodenum of post-weaning gilts. Methods: Forty post-weaning gilts were randomly allocated to four groups and fed diets supplemented with 0, 0.5, 1.0, or 1.5 mg/kg ZEA. Results: The results showed significant reductions in the activity of the antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, Nrf2 immunofluorescence showed that ZEA significantly induced the increase of Nrf2 gene expression in the cells, and Nrf2 transferred from the cytoplasm to the nucleus. Nrf2 expression reached its maximum level in the ZEA40 treatment group, which was consistent with our previous results in the pig intestine [11][12][13]. As a result, we think that ZEA can activate the Keap1-Nrf2 signaling pathway of IPEC-J2 cells, and the activation of this pathway increases the ability of IPEC-J2 cells to resist ZEA toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, Nrf2 immunofluorescence showed that ZEA significantly induced the increase of Nrf2 gene expression in the cells, and Nrf2 transferred from the cytoplasm to the nucleus. Nrf2 expression reached its maximum level in the ZEA40 treatment group, which was consistent with our previous results in the pig intestine [11][12][13]. As a result, we think that ZEA can activate the Keap1-Nrf2 signaling pathway of IPEC-J2 cells, and the activation of this pathway increases the ability of IPEC-J2 cells to resist ZEA toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…The relative expression of ROS mRNA and protein as well as the MDA content in the cells were dramatically raised following ZEA treatment of IPEC-J2 cells for 24 h and 36 h in this investigation, whereas the activities of the antioxidant enzymes T-SOD and GSH-PX were significantly decreased. ZEA promotes a large number of cells in a state of oxidative stress, which is consistent with our previous research results in the pig intestine [11][12][13]. Some studies also found that the level of ROS in human embryonic kidney cells exposed to ZEA for 1 h did not change significantly, but it increased significantly after 2 h [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Caco-2 cells, it was found that 100 μM QUE could protect the cell barrier function by inhibiting CHOP gene expression and suppressing the Bax/Bcl2 ratio, thereby inhibiting indomethacin- and diclofenac-induced apoptosis [ 39 ]. Different reports have also been published regarding in vivo studies in gilts, showing that ZEA alters the expression of key genes and proteins in the Nrf2 signaling pathway of duodenum and can resist ZEA-induced intestinal oxidative stress [ 40 ]. In contrast to the present study in an in vitro model, the combined effects of LPS and ZEA, which did not resist oxidative stress, may be simultaneous.…”
Section: Discussionmentioning
confidence: 99%
“…Zearalenone and its metabolites are classified as xenoestrogens due to their structural similarity to endogenous estrogens [ 2 , 3 ]. Previous studies have shown that ZEN exposure can induce an immune response, oxidative damage, and other pathological changes in different tissues of the body, causing organ damage, decreased productive and reproductive performance, and even acute animal death in severe cases [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%